Mobile brain/body Imaging in dance: A dynamic transdisciplinary field for applied research. (3rd July 2020) - Barnstaple, Rebecca; Protzak, Janna; DeSouza, Joseph F.X.; Gramann, Klaus
Abstract: Neuroscience of dance is an emerging field with important applications related to health and well‐being, as dance has shown potential to foster adaptive neuroplasticity and is increasingly popular as a therapeutic activity or adjunct therapy for people living with conditions such as Parkinson's and Alzheimer's diseases. However, the multimodal nature of dance presents challenges to researchers aiming to identify mechanisms involved when dance is used to combat neurodegeneration or support healthy ageing. Requiring simultaneous engagement of motor and cognitive domains, dancing includes coordination of systems involved in timing, memory and spatial learning. Studies on dance to this point rely primarily on assessments of brain dynamics and structure through pre/post‐tests or studies on expertise, as traditional brain imaging modalities restrict participant movement to avoid movement‐related artefacts. In this paper, we describe the process of designing and implementing a study that uses mobile brain/body imaging (MoBI) to investigate real‐time changes in brain dynamics and behaviour during the process of learning and performing a novel dance choreography. We show the potential for new insights to emerge from the coordinated collection of movement and brain‐based data, and the implications of these in an emerging field whose medium is motion. Abstract : Mobile brain/body imaging (MoBI) offers novel means of investigating complex human phenomena. We describe the process of designing and running a transdisciplinary study implementing MoBI to probe neural dynamics and processes involved in learning dance, a highly multimodal process involving coordinated cognitive‐motor effort. This study exemplifies the potential for new insights to emerge from the combined collection of brain and behavioural data in dynamic situations.